Principal leaderhip and students’ achievement: Mediated pathways of professional community and teachers’ instructional practices - Nedim Özdemir (KEDI journal of educational policy, 2019)
The aim of this study is to investigate the influence of principals’ leadership behaviors on students’ math achievements via professional community and teachers’ instructional practices in economically disadvantaged environments in lower secondary education. The study was completed in 36 lower secondary public schools located in Altındağ and Mamak boroughs in the city of Ankara, Turkey. A two-level quantitative research design was used to conduct this study. The data was analyzed through school-level factors such as professional community and teachers’ instructional practices. Research findings underline that principals’ leadership behaviors have indirect positive effects on students’ math achievements with the mediating role of math teachers. Principals should recognize and enhance the improvement of teachers' shared responsibility and deprivatized practices to increase the quality of instruction and student achievement. KCI Citation Count: 27